2003
DOI: 10.1002/jbm.a.20015
|View full text |Cite
|
Sign up to set email alerts
|

Design and fabrication of standardized hydroxyapatite scaffolds with a defined macro‐architecture by rapid prototyping for bone‐tissue‐engineering research

Abstract: This investigation describes the production and characterization of calcium phosphate scaffolds with defined and reproducible porous macro-architectures and their preliminary in vitro and in vivo bone-tissue-engineered response. Fugitive wax molds were designed and produced using a rapid prototyping technique. An aqueous hydroxyapatite slurry was cast in these molds. After sintering at 1250°C and then cleaning, dimensional and material characterizations of the scaffolds were performed. The resulting scaffolds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(136 citation statements)
references
References 34 publications
4
127
0
5
Order By: Relevance
“…19,23,25 This machine could precisely control the slice thickness using 2 thermoplastic materials. The lost mold technique we used was based on selective solubility of 2 materials in different solvents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19,23,25 This machine could precisely control the slice thickness using 2 thermoplastic materials. The lost mold technique we used was based on selective solubility of 2 materials in different solvents.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach using the SFF technique is to fabricate temporarily negative molds and cast the scaffold by using biomaterial suspensions. [16][17][18] Based on the original scaffold design, negative molds were removed after they were cast by biomaterials such as collagen, 19 ceramics, [20][21][22][23] polymers, 24 or their composites. 25 Several studies have demonstrated that this method was capable of fabricating scaffolds with controlled internal structures as well as external shapes.…”
Section: Introduction Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, there are many reviews on this subject [83][84][85][86][87][88][89] . Numerous studies have focused on producing 3D printed bone regenerative scaffolds (or substitutes) in a customdesigned manner [90,91] .…”
Section: Large Organ 3d Bioprintingmentioning
confidence: 99%
“…Ceramics are well known to induce differentiation of potentially osteogenic cells towards the osteogenic lineage [62][63][64][65][66][67] and they are able to bridge large bony defects in human if combined with MPC [68]. Even if it seems to be possible to design a standardized hydroxyapatite ceramic scaffold with the help of rapid prototyping techniques [69], the architecture of a given scaffold (i.e., the size and the interconnectivity of the pores) as well as the mechanical properties can be controlled much…”
Section: Three-dimensional Scaffoldsmentioning
confidence: 99%